2020
DOI: 10.1111/apps.12274
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Supervisor Knowledge Hiding in Organizations: A Multilevel Mediation Analysis

Abstract: Drawing on the theoretical framework of social cognitive theory, our study explores the multilevel mediation model in which moral disengagement (level‐1) mediates the direct relationships between knowledge hiding by supervisors from subordinates (KHSS: level‐2) and supervisor directed organizational citizenship behavior (SOCB: level‐1) and supervisor directed silence (SS: level‐1). Drawing on multi‐sourced, multi‐timed, and multilevel data of 306 subordinates nested within 83 supervisors, multilevel structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(75 citation statements)
references
References 58 publications
1
64
0
10
Order By: Relevance
“…In terms of individual-level results, the existing research has examined the effects of knowledge hiding on individual job performance, psychological status and attitude, workplace behavior, and supervisor-subordinate/coworker relationships. For instance, most studies have found that knowledge hiding among colleagues and between supervisors and subordinates can reduce task performance, organizational citizenship behavior (OCB), and creativity (Connelly et al, 2012;Cerne et al, 2014;Arain et al, 2019Arain et al, , 2020aJahanzeb et al, 2019;Malik et al, 2019;Singh, 2019;Zhu et al, 2019).…”
Section: Consequencesmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of individual-level results, the existing research has examined the effects of knowledge hiding on individual job performance, psychological status and attitude, workplace behavior, and supervisor-subordinate/coworker relationships. For instance, most studies have found that knowledge hiding among colleagues and between supervisors and subordinates can reduce task performance, organizational citizenship behavior (OCB), and creativity (Connelly et al, 2012;Cerne et al, 2014;Arain et al, 2019Arain et al, , 2020aJahanzeb et al, 2019;Malik et al, 2019;Singh, 2019;Zhu et al, 2019).…”
Section: Consequencesmentioning
confidence: 99%
“…In addition, both evasive hiding and rationalized hiding will hinder innovation performance. Regarding psychological status and attitudes, research suggests that knowledge hiding increases employees' moral disengagement (Arain et al, 2020a) and decreases their psychological safety, well-being, job satisfaction, and sense of thriving (Jiang et al, 2019;Offergelt et al, 2019;Khoreva and Wechtler, 2020). Furthermore, knowledge hiding can trigger knowledge seekers' deviant behaviors, turnover intention, upward silence, and non-engagement in knowledge sharing (Connelly and Zweig, 2015;Offergelt et al, 2019;Singh, 2019;Arain et al, 2020a).…”
Section: Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have sought to develop a research model that integrates motivational characteristics [16,23], the big five personality types [12], and leadership styles that influence knowledge hiding [24]. We assume that one of the major causes of knowledge hiding is relationship conflict, which creates aggressiveness in the personality and eventually leads to knowledge hiding.…”
Section: Introductionmentioning
confidence: 99%
“…KH takes place among coworkers (Aljawarneh and Atan 2018), team members (Babic et al 2019;Singh 2019), and even between supervisors and subordinates (Butt 2019) for various reasons (Afshar-Jalili et al 2020). Studies have found that KH is not only a hindrance to knowledge sharing (Qureshi and Evans 2015;Liu et al 2020a) but is also detrimental to organizations, as it can affect a firm's decision-making quality (Ghasemaghaei and Turel 2021), idea implementation (Li et al 2020), organizational performance, team performance (Chatterjee et al 2021), and creativity (Bogilovic et al 2017;Fong et al 2018;Peng et al 2019), in addition to employees' turnover intention (Serenko and Bontis 2016) and organizational citizenship behaviors (Arain et al 2020). KH also affects the internal and external stakeholders in an organization by affecting, for example, employees' abilities to solve customer problems, relationship building with customers (Chaker et al 2020), creativity (Rhee and Choi 2017), and job (Chatterjee et al 2021;Wang et al 2018b;Jahanzeb et al 2020) and innovation performance (Khoreva and Wechtler 2020).…”
Section: Introductionmentioning
confidence: 99%